Reconstructing the confluence zone between Laurentide and Cordilleran ice sheets along the Rocky Mountain Foothills, south‐west Alberta. (27th October 2016) - Utting, Daniel J.; Atkinson, Nigel; Pawley, Steven; Livingstone, Stephen J.
ABSTRACT: Landform mapping near the Athabasca valley was fundamental to determining whether the Late Wisconsinan Laurentide and Cordilleran Ice Sheets (LIS, CIS) coalesced. In this paper we examine the detailed landform record using new LiDAR digital elevation and hillshade models of the area of confluence and eventual desuturing of these ice sheets. This work reveals an earlier more extensive Cordilleran advance before coalescence with the LIS. When the ice sheets coalesced, the flow pattern was dominated by ice flow along the mountain front, with Cordilleran ice flowing out of major trunk valleys but Laurentide ice flowing into the Foothills up smaller valleys. This flow pattern implies that when the ice sheets coalesced the CIS was already waning, or at least was not at its maximum. Deglaciation was interrupted by several re‐advances, probably related to the destabilizing effect of proglacial lakes along the ice margin.